2003
DOI: 10.1002/srin.200300231
|View full text |Cite
|
Sign up to set email alerts
|

A Contribution to Scale Growth during Hot Rolling of Steel

Abstract: This work was carried out in context with the development of strip casting by the single-belt process. In this new process the casting is directly connected with hot rolling which must be carried out at lower speed than in conventional hot rolling, to match the casting rate. It is of interest to theoretically study the effect of low rolling speed on operational parameters and materials behaviour, among them scale formation. In the present investigation it is demonstrated that, under the conditions of hot rolli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…8) As a consequence, the analysis of the influence of temperature and time on oxidation rate, phase composition and morphology of the secondary and tertiary scales is of great interest in order to better understand work roll wear and strip surface defects in hot strip rolling.…”
Section: Introductionmentioning
confidence: 99%
“…8) As a consequence, the analysis of the influence of temperature and time on oxidation rate, phase composition and morphology of the secondary and tertiary scales is of great interest in order to better understand work roll wear and strip surface defects in hot strip rolling.…”
Section: Introductionmentioning
confidence: 99%
“…During the initial linear stage, the rate-controlling process for oxidation is oxygen diffusion through a gas phase boundary layer. 23,25) After the transition, the rate controlling step is diffusion of iron ions through the wüstite layer.…”
Section: Oxidation Behaviormentioning
confidence: 99%
“…Before the cold rolling or the galvanizing process, the strip must be completely removed to ensure the surface quality of the finished product [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…π F Ec    (2) Here, γ is the fracture surface energy. Nagl and Evans [10] analyzed the relationship between the cracking behavior and the thickness of scales under tension and found that the cracking stress/strain decreases with increasing thickness.…”
Section: Introductionmentioning
confidence: 99%